Analisis Perbandingan Strategi Diferensiasi, Service Quality, Keunggulan Bersaing POS Dan JNE Kabupaten Sukabumi - Mochamad Anton Wiguna Saputra; R. Deni Muhammad Danial; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine whether there are differences in differentiation strategies, service quality, and competitive advantages of Pos Indonesia and JNE in Sukabumi Regency. The method used in this research is quantitative with a comparative approach. The research population is customers who use Pos Indonesia and JNE delivery services in Sukabumi Regency which have an infinite population. Through Isaac and Michael's formula, it was determined that a sample of 272 people was divided into two, namely 136 Pos Indonesia users and 136 JNE users. The research data collection technique used a questionnaire with data analysis through the Mann Whitney test. Based on the results of the study, it can be seen that there is a significant difference between the differentiation strategy of Pos Indonesia and JNE in Sukabumi Regency, there is a significant difference between the service quality of Pos Indonesia and JNE of Sukabumi Regency, and there is a significant difference between the competitive advantages of Pos Indonesia and JNE in Sukabumi Regency. Keywords: Differentiation Strategy, Service Quality, Competitive Advantage